Pengawasan Dewan Perwakilan Rakyat Daerah terhadap Kawasan Tanpa Rokok: Studi Pengawasan Peraturan Daerah Nomor 2.A Tahun 2016 tentang Kawasan Tanpa Rokok di Kabupaten Pesawaran - Ririn Anjarwati; Bendi Juantara; Budi Harjo (Penerbit Goodwood, 2022)
Purpose: This study is to find out how the DPRD supervises the regional regulations. Method: This study used is qualitative, data collected through interviews, observation, and documentation. According to McCubbins and Schwartz (1984:65- 179), the theory used is Police-patrol oversight and Fire-alarm oversight. Results: This study reveal that DPRD in carrying out supervision is in accordance with its function, but the implementation of this supervision was only at the beginning of regional regulation number 2. In 2016 the no smoking area was ratified, no more intensive supervision was carried out, and there were no standard rules that could serve as guidelines for supervision by the DPRD in carrying out its functions. So that the results obtained, the supervision carried out by the Pesawaran Regency DPRD on the Non-Smoking Area does not work. Limitation: This research is how is the supervision of the Regional House of Representatives (DPRD) of Pesawaran Regency against Regional Regulation Number 2.a of 2016 concerning Non-Smoking Areas?